Jack S. Kilby papers - Kilby, Jack S., 1923-
Correspondence, memoranda, patents and related material, drawings, blueprints, transparencies, photographs, subject files, speeches, writings, newspaper clippings, and printed matter relating primarily to Kilby's inventions and projects while an engineer and later a consultant for Texas Instruments Incorporated. Kilby's inventions include the monolithic integrated circuit, also know as the chip or microchip. The papers also document Kilby's work as a consultant and adviser to the GM Hughes Electronic Corporation, Semiconductor Research Corporation, and the U.S. Dept. of Defense.
Subjects include capacitors; circuits; electronic miniature calculators; electrostatic display system; Kilby's teaching machine and system; microelectronics; military, industrial, and commercial applications of microchip technology; military service with the U.S. Army Signal Corps and deployment with the Office of Strategic Services to Burma, India, and China during World War II; particles; patents; semiconductors; a solar energy project, Project Illinois, using silicon technology to generate electrical power; telephone answering devices and telephone and paging devices; and the wristwatch.
Correspondents include Willis Adcock, J.F. Bucy, Janet K. Cameron, Stephen P. Emmons, Al Gross, Patrick E. Haggerty, Kazuo Hashimoto, Peter Johnson, Ann Kilby, Jane Kilby, Jay W. Lathrop, Charles H. Phipps, and Wilbur A. Porter.
Library of Congress General Collection.
Library of Congress Prints and Photographs Division.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Engineer and inventor. Full name: Jack St. Clair Kilby. Died 2005.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adcock, Willis -- Correspondence; Bucy, J. F. -- Correspondence; Cameron, Janet K. -- Correspondence; Emmons, Stephen P. -- Correspondence; Gross, Al -- Correspondence; Haggerty, Patrick E. -- Correspondence; Hashimoto, Kazuo, -- -1995 -- Correspondence; Johnson, Peter -- Correspondence; Kilby, Ann -- Correspondence; Kilby, Jane, -- -2004 -- Correspondence; Lathrop, Jay W. -- Correspondence; Phipps, Charles H. -- Correspondence; Porter, Wilbur A. -- Correspondence; United States. -- Army. -- Signal Corps; United States. -- Department of Defense; United States. -- Office of Strategic Services; GM Hughes Electronic Corporation; Semiconductor Research Corporation; Texas Instruments Incorporated; Electric power; Electrostatics; Calculators; Capacitors; Integrated circuits; Microelectronics; Particles; Patents; Radio paging; Semiconductors; Silicon; Solar energy; Telephone answering and recording apparatus; World War, 1939-1945 -- Burma; World War, 1939-1945 -- China; World War, 1939-1945 -- India; Wrist watches; Engineers; Inventors